2020
DOI: 10.1007/s10570-020-03078-w
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating graphene oxide into biomimetic nano-microfibrous cellulose scaffolds for enhanced breast cancer cell behavior

Abstract: The impact of graphene oxide (GO) on normal cells has been widely investigated. However, much less is known on its effect on cancer cells. Herein, GO nanosheets were incorporated into electrospun cellulose acetate (CA) microfibers. The GOincorporated CA (GO/CA) microfibers were combined with bacterial cellulose (BC) nanofibers via in situ biosynthesis to obtain the nano-microfibrous scaffolds. The GO/CA-BC scaffolds were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…2A) reveal the fibrous structure of CA, BNC, CA/ BNC, and CA/BNC-H grafts. CA has thick electrospun fibers and BNC shows nanofibrous and porous morphology, in consistent with previous reports [31,32]. CA/BNC and CA/BNC-H show entangled dual fibers of thick CA fibers and fine BNC fibers.…”
Section: Characterization Of Ca/bnc-h Graftssupporting
confidence: 92%
“…2A) reveal the fibrous structure of CA, BNC, CA/ BNC, and CA/BNC-H grafts. CA has thick electrospun fibers and BNC shows nanofibrous and porous morphology, in consistent with previous reports [31,32]. CA/BNC and CA/BNC-H show entangled dual fibers of thick CA fibers and fine BNC fibers.…”
Section: Characterization Of Ca/bnc-h Graftssupporting
confidence: 92%
“…In the case of cancer cells, proliferation was adjusted to enable the formation of 3D spheroids of cancer cells and long-term cell culture. Graphene derivatives regulate the microenvironments of target cells Recently, Wan et al also reported that GO exerts a positive effect on the growth of cancer cells when incorporated with the scaffold structure [119]. In this study, a scaffold consisting of cellulose acetate (CA) microfibers in combination with bacterial cellulose (BC) was fabricated, and GO was further added to the CA-BC scaffold.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Wan et al also reported that GO exerts a positive effect on the growth of cancer cells when incorporated with the scaffold structure [ 119 ]. In this study, a scaffold consisting of cellulose acetate (CA) microfibers in combination with bacterial cellulose (BC) was fabricated, and GO was further added to the CA-BC scaffold.…”
Section: Controlling 3d Cancer Cell Microenvironments Using Graphementioning
confidence: 99%
“…Natural biopolymers owing to their low toxicity, biodegradability, renewability, environmental sensitivity, and biocompatibility are also promising materials to improve the biological properties of graphene-based materials. [142][143][144][145] Chitosan with anticancer activity and as a pH sensitive polymer has been widely employed in the synthesis of polymergraphene hybrids. [146][147][148] The produced multifunctional scaffolds have exhibited high loading capacities and functional binding sites for different types of drugs and targeting ligands.…”
Section: Graphene-polymer Platforms In Drug Deliverymentioning
confidence: 99%